Pengembangan Website Profil Sekolah sebagai Media Informasi di SD Negeri 76 Kota Bengkulu - Abdullah, Dedy; Yuliantoro, Tri Witono; Radika, Agung Cessar; Wijaya, Pasya Ahmad; Gunawan, Anta Ramatio; Ibrahim, Jhesen Marlino (Pakis Journal Institute, 2025)
The development of a school profile website is a crucial solution to enhance transparency and information accessibility in the digital era. This study aims to design and implement a school profile website for SD Negeri 76 Kota Bengkulu, focusing on creating an effective and efficient medium for information dissemination. The research employs a systematic approach, including needs analysis, system design, website development, and user evaluation. The needs analysis phase involved gathering input from school stakeholders, including teachers, students, and parents, to identify key features and content requirements. The design phase focused on creating a user-friendly interface with intuitive navigation, while the development phase utilized modern web technologies such as HTML, CSS, and JavaScript, along with a content management system (CMS) for easy updates. The evaluation phase involved testing the website's functionality, responsiveness, and usability with a group of end-users. The results indicate that the developed website successfully meets the school's needs by providing comprehensive information, including the school's profile, vision and mission, flagship programs, student achievements, and academic as well as non-academic activities. Additionally, the website is equipped with interactive features such as photo galleries, activity blogs, and online contact forms to facilitate better communication between the school and the community. User feedback highlights the website's ease of access, responsiveness across various devices, and effectiveness in improving information transparency. The study concludes that the school profile website not only enhances the school's digital presence but also contributes to building a positive image and attracting prospective students. Future work may include integrating advanced features such as real-time updates, event calendars, and parent-teacher communication portals to further improve the website's functionality and user engagement.